2019
DOI: 10.1021/acs.analchem.9b04424
|View full text |Cite
|
Sign up to set email alerts
|

Ion Current Rectification in High-Salt Environment from Mesoporous TiO2 Microplug in Situ Grown at the Tip of a Micropipette Induced by Space-Confined Evaporation

Abstract: In this work, in situ growth of a titanium dioxide microplug (TDMP) having mesoporous channels at the tip of a glass micropipette induced by space-confined evaporation is reported. Moreover, clear ion current rectification (ICR) of a single-material nanopore in a saturated potassium chloride solution is observed for the first time. TDMP presents an asymmetrical channel structure with the top and bottom apertures of 12.3 ± 6.1 and 42.6 ± 19.7 nm, respectively. TDMP exhibits outstanding ICR capability as the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Thus, a decreased rectification ratio of Au/H3/mPEG-modified nanopores can be observed in comparison with that of Au/H3-modified nanopores, as shown in Figure d. Subsequently, a higher normalized ionic current change to the addition of miRNA-155 can be expected since the background ionic current is reduced, while the responsive probes remain unchanged. Second, mPEG molecules may enhance the thermal stability of the hybridizations of H1, H2, and H3 due to the molecular crowding effect, which eventually contribute to the sensing performance of the sensor. Third, mPEG molecules partition H3 probes and lower the interference among hybridizations, so that the efficiency and rate of hybridization can be improved. This result indicated that Au/H3/mPEG-modified nanopores can give a significant response to miRNA-155.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, a decreased rectification ratio of Au/H3/mPEG-modified nanopores can be observed in comparison with that of Au/H3-modified nanopores, as shown in Figure d. Subsequently, a higher normalized ionic current change to the addition of miRNA-155 can be expected since the background ionic current is reduced, while the responsive probes remain unchanged. Second, mPEG molecules may enhance the thermal stability of the hybridizations of H1, H2, and H3 due to the molecular crowding effect, which eventually contribute to the sensing performance of the sensor. Third, mPEG molecules partition H3 probes and lower the interference among hybridizations, so that the efficiency and rate of hybridization can be improved. This result indicated that Au/H3/mPEG-modified nanopores can give a significant response to miRNA-155.…”
Section: Resultsmentioning
confidence: 97%
“…UV light induced superwettability and inhibited ion transmission under positive voltage, while it promoted ion transmission under negative voltage. Liu et al [99] reported TiO 2 microspheres with mesoporous channels that were grown in situ at the tips of glass microtubes by confined space evaporation. The TiO 2 micro-plug with asymmetric mesoporous channel showed strong ion current rectification abilities even in a saturated KCl solution.…”
Section: Nanochannels For Ion Rectificationmentioning
confidence: 99%
“…A thorough understanding of these concepts is crucial for the effective management of soil carbon and the implementation of sustainable land-use practices (Banwart et al, 2014). One important aspect to consider is the coexistence of mesopores and nanopores between parallel smectite particles, which has a significant impact on soil permeability (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%